An evaluation of the Safety Management System compliance amongst Malaysian major hazard industries - Mohd Noordin, Mohd. Hazim (2000)
An evaluation of the Malaysian major hazard industries (MHI) compliance towards the OSHA requirement on Safety Management System (SMS) was undertaken. The research was carried out via documentary reviews on the individual company Safety Reports submitted to the Department of Occupational Safety and Health (DOSH) under the Control oflndustrial Major Accident Hazards (CIMAH) Regulation of the Occupational Safety and Health Act (OSHA) 1994. Out of the available one hundred fourteen (114) Safety Reports containing the SMS information, forty (40) MHI reports were sampled. Given that MHIs have the potential to cause potential major accident hazards within and outside their boundaries, one of the main objectives of this evaluation is to assess the MHl compliance towards the SMS requirement. The evaluation revealed that the level of compliance meets the minimum requirement. However, the overall mean score of 2.75 at standard deviation of l.6 barely passes the median value of 2.5. Of the sampled assessed, only 48% data falls within I standard deviation, thus the samples chosen were almost representative of the MHI population. , The compliance is based on six main Management System Information (MSI) elements against twelve main Installation Demographic Information (101) categories. The high levels of compliance were exhibited by; • LPG storage plants as compared to other oil, gas, chemical, insecticides manufacturing plants. Manufacturing industry involved in the use of flammable as compared to toxic, reactive or explosive substances. Organisation having worker population of between 300 to 500. Organisation having expatriate management but with local operations personnel Multinational companies with foreign technology. Organisation that have been in operations between 6 to 10 years ago. • Organisations that are certified to the ISO quality system. Some of the sample assessed did exhibit a structured management system approach as required, however others only have disjointed safety programme and procedures to manage their safety and health issues. The next step forward for these organisations to formally structure these practices into a coherent and holistic system approach as required. The evaluation had also revealed that there were many approaches in the development of SM_S ranging from codes, standards, industry practices, legislation and international safety organisations. It was recognised that every organisation is unique in its own ways, as such there is no hard and fast rule on what would be the best SMS model for the respective organisation. The main aim is to have a SMS that is simple yet comprehensive to meet all foreseeable circumstances specific to the organisation and at the same time be flexible enough to be verified and accredited to an internationally accepted standards, where possible.